Autophagy Induced by Simian Retrovirus Infection Controls Viral Replication and Apoptosis of Jurkat T Lymphocytes - Jingting Zhu; Lingyan Yang; Qibo Zhang; Jia Meng; Zhi-Liang Lu; Rong Rong (Viruses, 2020)
Autophagy and apoptosis are two important evolutionarily conserved host defense mechanisms against viral invasion and pathogenesis. However, the association between the two pathways during the viral infection of T lymphocytes remains to be elucidated. Simian type D retrovirus (SRV) is an etiological agent of fatal simian acquired immunodeficiency syndrome (SAIDS), which can display disease features that are similar to acquired immunodeficiency syndrome in humans. In this study, we demonstrate that infection with SRV-8, a newly isolated subtype of SRV, triggered both autophagic and apoptotic pathways in Jurkat T lymphocytes. Following infection with SRV-8, the autophagic proteins LC3 and p62/SQSTM1 interacted with procaspase-8, which might be responsible for the activation of the caspase-8/-3 cascade and apoptosis in SRV-8-infected Jurkat cells. Our findings indicate that autophagic responses to SRV infection of T lymphocytes promote the apoptosis of T lymphocytes, which, in turn, might be a potential pathogenetic mechanism for the loss of T lymphocytes during SRV infection.